Pengaruh Model Pembelajaran Two Stay Two Stray (TSTS) terhadap Hasil Belajar Peserta Didik pada Sekolah Penggerak (Mata Pelajaran Ekonomi). - Qotrunnada, Alisa Beta; Andriansyah, Eka Hendi (Universitas Negeri Surabaya, 2024)
Differentiated and innovative learning is one of the challenges for sekolah penggerak to held in the learning processsaccording to the curriculum of Merdeka. This study aims to determine the effect of the Two Stay Two Stray (TSTS) learning model on student's learning outcomes in market balance material. The classical assumption test technique is applied to the data and then analyzed using simple regression. The results of this study show that the Two Stay Two Stray (TSTS) learning model has a significant effect on improving student's learning outcomes based on the normality test, multicollinearityytest, heteroscedasticity test, autocorrelation test, and linearity test.